Russula neoelpidensis, a new sequestrate species and member of the Badia subclade within the Integrae clade - Miller, Steven L.; Cotter, Henry Van T. (Phytotaxa, 2025)
In this paper, we describe a new species of sequestrate Russula (Macowanites), R. neoelpidensis, from the southeastern United States using a combined approach of morphological characterization and phylogenetic analyses. Our molecular analysis places R. neoelpidensis in the crown clade in a well-supported Badia subclade nested within Integrae. Russula neoelpidensis contains the pink or red staining of the incrustations in Sulfovanillin, which is present in the majority of the analyzed species of Integrae, as well as incrustations in Basic Fuchsin that are not acid resistant. Russula neoelpidensis was found in a mixed bottomland hardwood forest containing oaks which may be its ectomycorrhizal partner. Russula neoelpidensis is an interesting species with characteristics that both support and extend synapomorphies that could help refine and define formal subgeneric classification systems.